La Exigibilidad e Incorporación de Enfermedades Profesionales en la Ley de Seguridad Social - Delgado Sarmiento, David Alejandro (2020)
The present research presented under the thesis modality refers to a legal problem that deserves to be transformed to solve and overcome the socio- legal problem identified in article 34 of the Constitución de la República del Ecuador determines the Ley de Seguridad Social, in Article 326 numeral 5 of the ibid norm establishes the development of work activities in an adequate and conducive environment, guaranteeing health; The Código del Trabajo in its article 349 stipulates what occupational diseases are and in the ibid norm in article 363 a classification or a catalog of possible occupational diseases is displayed that are no longer in line with current employment, in that sense the relevant norm that is the Ley de Seguridad Social in Article 156 determines the contingencies covered by the General Occupational Risk Insurance and does not determine a requirement through the Law in order to bind the aforementioned institution to the study of any possible Occupational disease, in this sense, it is necessary to reform the Ley de Seguridad Social in its Title VII of the Seguro General de Riesgos del Trabajo in its Single Chapter modifying Article 156 to determine the enforceability and mandatory nature of the Institution for the study of any possible professional illness.